S114 Non-invasive assessment of lung inhomogeneity for early identification of COPD. (12th November 2019) - Smith, NMJ; Magor-Elliot, S; Redmond, J; Ritchie, GAD; Robbins, PA; Petousi, N; Talbot, NP
Abstract : Background: The current Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification of COPD is based upon FEV1. However, FEV1 reflects predominantly large airway dysfunction, whereas COPD is primarily a disease of the small airways. FEV1 is therefore relatively insensitive to early disease, making early diagnosis and intervention difficult. In contrast, lung inhomogeneity is an early feature of obstructive lung disease. We assessed a novel non-invasive method for estimating lung inhomogeneity in patients with COPD. Methods: Thirty patients with COPD (age 67±8 years, mean±SD) and ten healthy controls (70±4 years) each underwent at least one nitrogen multi-breath washout test (10 min breathing air, 5 min breathing O2 ) during normal relaxed breathing. Respired gas composition was measured every 10 msec using a highly-accurate in-airway gas analyser based on laser absorption spectroscopy. A mathematical model of the lung was subsequently fitted to the entire respiratory gas profile to estimate the distribution of lung compliance, relative to lung volume, across 125 theoretical lung units. The standard deviation of this distribution (σCL:VA) is a measure of regional variation in lung compliance. Results: The test was well-tolerated. Figure 1 demonstrates the relationship between GOLD stage, defined by FEV1, and our novel index of inhomogeneity, σCL:VA. Compared with healthy controls, σCL:VA was elevated 29 of the 30 patients with COPD. Importantly, σCL:VA was significantly elevated in patients with GOLD stage 1 (0.86±0.13 vs. 0.51±0.08; p<0.0001, unpaired t-test), despite the FEV1 being within the normal range (>80% predicted) in this group. Conclusion: These data confirm that a novel non-invasive method for assessing lung inhomogeneity is well-tolerated in patients with COPD across a wide range of disease severity, and that it is feasible in an outpatient setting. The parameter σCL:VA shows promise as an early marker of small airways dysfunction in COPD, which may identify disease earlier than spirometry. Future work will assess the relationship between σCL:VA and clinical measures of disease severity in COPD, and study changes with interventions.